The Agricultural Company Management and Environment - Baštýřová, Jiřina (2017)
The objective of the present thesis is to evaluate economic activities of a medium-sized agricultural farm in a real environment. The theoretical part of the thesis is engaged with the problems of the current scale of use of the landscape by farmers who continue to lay emphasis primarily on the economic function. Subsequently, in pursuance of our research, an alternative method of farming, i.e. organic farming, is described, along with the contemporary situation of this sphere in the Czech Republic. The last chapter of the theoretical part examines the Common Agricultural Policy of the EU and the tools thereof. In the framework of our research, the area of interest in which the farm observed works is described, and processes of the farm´s economic activities and economic evaluation are delineated. Next, environmentally-friendly landscape measures are proposed which take into consideration both the ecologic and social functions. This method of farming is evaluated in terms of economy and this evaluation includes an outline of the problems of the system of subsidies